Indirect decompression and reduction of lumbar spondylolisthesis does not result in higher rates of immediate and long term complications. (November 2017) - Januszewski, Jacob; Beckman, Joshua M.; Bach, Konrad; Vivas, Andrew C.; Uribe, Juan S.
Highlights: MIS techniques have been associated with higher rates of neurological complications in spondylolisthesis reduction surgery. A retrospective review of 269 patients and 54 spondylolisthesis levels that met inclusion criteria was conducted. 9.6% of patients experienced postoperative anterior thigh numbness, which completely resolved within 3 months. 3.8% of patients suffered a transient foot weakness that resolved by 3 months follow-up. MIS technique for spondylolisthesis reduction is safe, reproducible, and durable. Abstract: Nerve root decompression and spondylolisthesis reduction is typically reserved for open surgery. MIS techniques have been thought to be associated with higher rates of neurological complications. This study aims to report acute and chronic neurologic complications encountered with MIS surgery for spondylolisthesis, specifically, the incidence of nerve root injury and clinical and radiographic outcomes. A retrospective review of 269 patients who underwent MIS LIF or ALIF treatment for lumbar degenerative or isthmic grade 1 or 2 spondylolisthesis was conducted. Immediate and long-term complication rates were the primary outcome. Only patients who had symptomatic anterolisthesis and 2-year outcome data were included in the study. 52 patients met inclusion criteria with 54 lumbar spondylolisthesis levels treated. Five patients (9.6%) experienced postoperative anterior thigh numbness, which completely resolved within 3 months. There were no permanent neurologic deficits; however, 2 patients (3.8%) suffered a transient foot weakness that resolved with physical therapy by 3 months follow-up. There was one incidence of wound breakdown that required revision and one incidence of L5/S1 endplate/sacral promontory fracture and relisthesis 3 months postoperatively. Overall fusion rate was 98% at 6 months. Indirect decompression and closed anatomical reduction for treatment of low-grade spondylolisthesis using ALIF and LIF with posterior percutaneous fixation was not associated with an increased risk of neurologic deficit. This study suggests that this technique is safe, reproducible, durable, and provides adequate fusion rates.